PENERAPAN KONSEP CITYWALK PADA BEACHWALK SHOPPING CENTER BALI - Al Mauludy, Yoru Rizqi; Fitriyanto, Dominikus Aditya (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
The island of Bali is the main tourist destination in Indonesia, which makes this island busy with world tourists. The increase in tourist visits also has an impact on the provision of infrastructure on the island of Bali, especially commercial facilities related to retail and entertainment, namely Shopping Centers. As times and people's lifestyles develop, people's perception of shopping centers has also evolved into a public space that can accommodate all visitor activities ranging from retail activities to entertainment. However, the provision of shopping center facilities sometimes does not pay attention to harmony with nature and its impact on the environment as well as aspects of user satisfaction. Changes in people's lifestyles and their relationship to nature and user satisfaction can be addressed by applying the CityWalk concept to shopping center buildings. Beachwalk Shopping Center which uses the citywalk concept is used as a research object to analyze its application. This research aims to understand the Beachwalk Shopping Center case study which applies the CityWalk concept in terms of the principles of the CityWalk concept such as user accessibility, green open space, transportation accessibility and building sustainability. The results of the research show that the building has implemented the principles of the CityWalk concept well through the presence of pedestrians areas as user accessibility, lots of green open spaces, aesthetic architectural design, minimal negative impact on the building and easy access to transportation in the BeachWalk Shopping Center Bali building.